2017
DOI: 10.1038/npp.2017.15
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Nicotine Strengthens Gamma Oscillations in the Prefrontal Cortex and Improves Visual Attention

Abstract: Nicotine has strong addictive as well as procognitive properties. While a large body of research on nicotine continues to inform us about mechanisms related to its reinforcing effects, less is known about clinically relevant mechanisms that subserve its cognitive-enhancing properties. Understanding the latter is critical for developing optimal strategies for treating cognitive deficits. The primary brain region implicated in cognitive functions improved by nicotine is the prefrontal cortex (PFC). Here we asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 56 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…In the following experiment, a separate group of rats was treated with nicotine following the same daily dosing regimen. Nicotine-treated rats performed significantly better in a visual attention task compared to controls, verifying the cognitive enhancing effects of nicotine [ 60 ]. In sum, nicotine administration increases gamma band activity.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the following experiment, a separate group of rats was treated with nicotine following the same daily dosing regimen. Nicotine-treated rats performed significantly better in a visual attention task compared to controls, verifying the cognitive enhancing effects of nicotine [ 60 ]. In sum, nicotine administration increases gamma band activity.…”
Section: Resultsmentioning
confidence: 93%
“…Recently, Bueno-Junior and colleagues examined the effects of acute versus chronic nicotine exposure on brain oscillatory activity in rats [ 60 ]. The authors implemented a daily dosing regimen of nicotine (0.2 mg/kg) in vivo and found that acute nicotine administration slightly increased gamma power and reduced theta and beta power.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurons were labeled as modulated or non-modulated based on stimulus reactivity through comparing pre-CS spike counts versus during-CS and post-US spike counts via one-tailed paired t-tests. Modulated neurons were then classified as excited (higher spike count) or suppressed (lower spike count) by each stimulus (CS or US) (Bueno-Junior et al, 2017Wood et al, 2012) (Figure 6B). The p-value of this categorization was Bonferroni corrected based on the total number of neurons from all groups (N = 110, p = 0.0004) ( Figure 6B).…”
Section: Single-unit Activitymentioning
confidence: 99%
“…[12][13][14][15] Both α4β2 and α7 nAChRs are expressed in the mPFC in a layer-specific manner; in layers 2/3, nAChRs are mainly expressed in γ-aminobutyric acid (GABA)-ergic interneurons, whereas in the deeper layers 5/6, both glutamatergic pyramidal neurons and GABAergic interneurons, as well as glutamatergic presynaptic terminals, express the nAChRs. [16][17][18] It has been reported that nicotineinduced enhancements of attention, working memory and recognition are associated with long-lasting activities of mPFC neurons. [19][20][21][22] Considering that the nicotine-induced potentiation of excitatory transmission in mPFC pyramidal neurons readily disappears due to a desensitization of nAChRs, 17,23) it was hypothesized that there exit other mechanism(s) that generates a persistent increase in mPFC neuronal activity.…”
Section: Introductionmentioning
confidence: 99%